Plunging to Earth: Once the sport of daredevils, skydiving now offers its existential thrills to grandmothers, pudgy geeks, and even the occasional college professor. - Zaretsky, Rob (American Scholar)
The author describes his experiences skydiving. He briefly examines his interest in skydiving, dating back to movie scenes depicting paratroopers landing in France during World War II. The author discusses his fears about jumping out of an airborne plane and relates his experiences in learning how to skydive and the importance of proper parachute use, jumpers arching the body for maximum stability in the air, and what not to do during dives in training sessions before his jump. The author also examines why human beings are drawn to such adventures and what motivates risk-taking. The author describes what went through his mind during his jump, what he did wrong, and the feeling of relief that he survived.